Post-purchase behavioral intention in medical aesthetic: the role of image, perceived value, and satisfaction - Ma, Chen-Chung; Ou, Tzu-Chi; Tsai, Chun-Mei; Chen, Tai-Hsiang (Frontiers in Public Health, 2025)
IntroductionThe technicality and professionalism of medical aesthetics have become one of the most fashionable indicators in the world, and image is the key factor of aesthetic development. This study aims to explore the relationship between medical aesthetic image, perceived value, satisfaction and post-purchase behavioral intention.MethodsThe subjects included customers who had consumed and received treatment in the three years, and the questionnaires were collected from returning clients of each unit in the medical aesthetic group from May 17, 2017 to May 31, 2017. We used the structural equation modeling (SEM) to analyze the data.ResultsThe results showed that medical aesthetic image was positively associated with perceived value, satisfaction and post-purchase behavioral intention; perceived value was positively associated with satisfaction and post-purchase behavioral intention; satisfaction was positively associated with post-purchase behavioral intention.DiscussionThis study can provide medical aesthetic practitioners with an understanding of consumers' image and perceived value to improve satisfaction. The changes in consumers' perception of aesthetic medicine can be evaluated more objectively, and suggestions can be provided for medical institutions to strengthen their cultural connotation and external image, so as to establish a strong brand image.